On the afterlife of things in artworks Doris Salcedo's "Atrabiliarios" and other contact relics : the twenty-first Horst Gerson Lecture held in memory of Horst Gerson (1907-1978) in the Aula of the University of Groningen on the 12th of October 2023 - Wagner, Monika 1944- (Horst Gerson Lecture Foundation, 2023)
The Twenty-First Horst Gerson Lecture held in memory of Horst Gerson (1907-1978) in the Aula of the University of Groningen on the 12th of October 2023. Everyday things, as they have increasingly led their afterlives in works of art since the 1960s, have a history of previous use attached to them. This made them particularly relevant for new artistic strategies developed in the context of the memorial debates since the 1980s. This publication is concerned with different forms of violence that are central to cultures of memory and explores how materials and things are made to talk about this in the new context of the artwork. Initially it is about European examples that - as in the case of Christian Boltanski and Sigrid Sigurdsson - revolved around the Holocaust. Methodologically, the focus is on analysing the semantics of the materials, an approach that offers options of connecting to works from other parts of the world for which other incidents and traumata form the frame of reference. In the afterlife of material things and their encounters with forms of violence, artists as diverse as Xu Bing, Romuald Hazoumé and Doris Salcedo, whose eponymous work is at the centre of the publication, meet. Edited by Simon FerdinandGraphic design by Rudo MengeCover photo: Doris Salcedo, Atrabiliarios, 1994-2004 Horst Gerson Lectures FoundationP.O. Box 716NL-9700 AS GroningenHorst Gerson Lectures
Keywords: Salcedo, Doris -- 1958-